Ownership structure, firm age, and technological capital as determinants of firm performance and value - Zulfikar Ikhsan Pane; Yustina Triyani; Ingkak Chintya Wangsih (Jurnal Ekonomi Perusahaan, 2025)
This study examines the effects of ownership structure, firm age, and technological capital on firm performance and firm value. Using a final sample of 99 observations from manufacturing sector companies in Indonesia over the period 2020–2022, the findings reveal that only firm age and technological capital have a positive and statistically significant effect on firm performance. Further analysis indicates only technological capital has a positive and significant effect on firm value. These results suggest that the longer a firm operates, the greater its production scale and cost-efficiency capabilities become; however, such maturity alone is insufficient to convince investors. In contrast, a firm’s ability to adapt to and develop technological capabilities not only enhances profitability but also increases its stock price in capital market.